Effect of SiC(111) with different layers on adsorption properties of CO molecules. (December 2020) - Lin, Long; Yao, Linwei; Li, Shaofei; Shi, Zhengguang; Xie, Kun; Zhu, Linghao; Tao, Hualong; Zhang, Zhanying
Abstract: Using the first-principles method, we studied the adsorption of CO molecules on SiC(111) surface with different layers. It is found that the adsorption of CO molecules on monolayer and bilayer SiC(111) surface is physical, while that on trilayer folded SiC(111) surface is chemical. The Si atom on the trilayer SiC(111) surface is the active adsorption site, and the O atom of the CO molecules prefers the Si atom on the SiC(111) surface. The calculated charge transfer and density of state (DOS) indicate that the electronic properties of the trilayer SiC(111) surface adsorbed CO molecules change. The trilayer SiC is promising for detecting CO molecules.